Regulation of cell proliferation by the guanosine–adenosine mechanism: role of adenosine receptors. Issue 2 (8th July 2013) - Jackson, Edwin K.; Gillespie, Delbert G.
Abstract A recent study (American Journal of Physiology – Cell Physiology 304:C406–C421, 2013) suggests that extracellular guanosine increases extracellular adenosine by modifying the disposition of extracellular adenosine ("guanosine–adenosine mechanism") and that the guanosine–adenosine mechanism is not mediated by classical adenosine transport systems (SLC28 and SLC29 families) nor by classical adenosine‐metabolizing enzymes. The present investigation had two aims (1) to test the hypothesis that the "guanosine–adenosine mechanism" affects cell proliferation; and (2) to determine whether the transporters SLC19A1, SLC19A2, SLC19A3, or SLC22A2 (known to carrier guanosine analogs) might be responsible for the guanosine–adenosine mechanism. In the absence of added adenosine, guanosine had little effect on the proliferation of coronary artery vascular smooth muscle cells (vascular conduit cells) or preglomerular vascular smooth muscle cells (vascular resistance cells). However, in the presence of added adenosine (3 or 10 μmol/L), guanosine (10–100 μmol/L) decreased proliferation of both cell types, thus resulting in a highly significant (P < 0.000001) interaction between guanosine and adenosine on cell proliferation. The guanosine–adenosine interaction on cell proliferation was abolished by 1, 3‐dipropyl‐8‐(p‐sulfophenyl)xanthine (adenosine receptor antagonist). Guanosine (30 μmol/L) increased extracellular levels of adenosine when adenosine (3 μmol/L) was added to the medium. This effect was not reproduced by high concentrations of methotrexate (100 μmol/L), thiamine (1000 μmol/L), chloroquine (1000 μmol/L), or acyclovir (10, 000 μmol/L), archetypal substrates for SLC19A1, SLC19A2, SLC19A3, and SLC22A2, respectively; and guanosine still increased adenosine levels in the presence of these compounds. In conclusion, the guanosine–adenosine mechanism affects cell proliferation and is not mediated by SLC19A1, SLC19A2, SLC19A3, or SLC22A2.